2014
DOI: 10.7897/2230-8407.050463
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Interaction of Green Tea Extract With Hydrochlorothiazide Against Isoproterenol Induced Myocardial Damage in Rats

Abstract: To evaluate the pharmacodynamic interaction of green tea extract with hydrochlorothiazide against isoproterenol induced myocardial infarction wistar albino rat of either sex were prophylactically treated with hydrochlorothiazide (10 mg/kg for 7 days), low and high dose of green tea extract (100 and 500 mg/kg for 3 weeks) and their combination by oral route. To induce the toxicity apart from normal control all other group subjected to isoproterenol (150 mg/kg, s.c) for two consecutive days. The effect of prophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 12 publications
6
14
0
Order By: Relevance
“…were observed in 100% of the rats in CT-ISO (Cardiotoxic group with isoproterenol). Similar type of observation was also made by some other researchers 15,17 . However, 55.56% of rats in CT-ISO-PRO (Cardiotoxic group with isoproterenol after propranolol treatment), 75% of rats in CT-ISO-P (Cardiotoxic group with isoproterenol after peanut treatment) and 88.89% of rats in CT-ISO-C (Cardiotoxic group with isoproterenol after combined treatment of peanut and propranolol) showed almost normal histological architecture of heart (photomicrograph 1).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…were observed in 100% of the rats in CT-ISO (Cardiotoxic group with isoproterenol). Similar type of observation was also made by some other researchers 15,17 . However, 55.56% of rats in CT-ISO-PRO (Cardiotoxic group with isoproterenol after propranolol treatment), 75% of rats in CT-ISO-P (Cardiotoxic group with isoproterenol after peanut treatment) and 88.89% of rats in CT-ISO-C (Cardiotoxic group with isoproterenol after combined treatment of peanut and propranolol) showed almost normal histological architecture of heart (photomicrograph 1).…”
Section: Resultssupporting
confidence: 88%
“…In the present study, the percent changes of body weight were almost similar to the findings reported by the various investigators from different countries 15 Again, in this study marked histological changes such as widespread myocardial disorganization improvement in histological architecture of isoproterenol induced cardiotoxic rats 18 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations